Natural History of the Gyrfalcon in the Central Canadian Arctic - Poole, K.G.; Bromley, R.G. (ARCTIC, 1988)
A population of breeding gyrfalcons was studied from 1982 to 1986 on a 2000 sq km area in the central Arctic of the Northwest Territories. Each year 14-18 territories were occupied. The mean internest distance was 10.6 km, giving one of the highest recorded densities for the species. There was a tendency for regularity in spacing of territories. Most (85%) nests were in abandoned stick nests of common ravens or golden eagles. Rough-legged hawk nests were not used by gyrfalcons, despite numerous available. Mean date of initiation of laying was 8 May. Mean size of clutch was 3.80 and of brood was 2.53, and mean productivity was 1.50 fledged young. A reduction of 48% from estimated number of eggs laid to number of fledglings was determined. Reproductive success declined with increased severity of spring weather, notably increased days and amount of precipitation.Key words: gyrfalcon (Falco rusticolus), natural history, reproductive ecology, central Arctic Mots clés: gerfaut (Falco rusticolus), histoire naturelle, écologie de la reproduction, région centrale arctique